Photoluminescence of barium titanate and barium zirconate in multilayer disordered thin films at room temperature - Moreira, M. L.; Gurgel, M. F. C.; Mambrini, G. P.; Leite, E. R.; Pizani, P. S. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Amer Chemical Soc, 2008)
The emission of wide band photoluminescence showed a synergic effect on barium zirconate and barium titanate thin films in alternate multilayer system at room temperature by 488 nm exiting wavelength. The thin films obtained by spin-coating were annealed at 350, 450, and 550 degrees C for 2 h. The X-ray patterns revealed the complete separation among the BaTiO3 and BaZrO3 phases in the adjacent films. Visible and intense photoluminescence was governed by BaZrO3 thin films in the multilayer system. Quantum mechanics calculations were used in order to simulate ordered and disordered thin films structures. The disordered models, which were built by using the displacement of formers and modifier networks, showed a different symmetry in each system, which is in accordance with experimental photoluminescence emission, thus allowing to establish a correlation among the structural and optical properties of these multilayered systems.